Low Computational Cost GNSS GPS/GLONASS Maximum Likelihood Bit Synchronization Method - Puga, Gerardo Ludovico (2012)
A maximum likelihood bit synchronization method is proposed for GNSS signals that works on multiple millisecond integrations. Since the amount of samples that need to be processed in order to achieve bit edge synchronization is decreased, the peak processor load is reduced as well. This method also presents lower error rate than other bit edge synchronization algorithms, while improving error rate performance under low signal-to-noise ratios. The method can be used with both GPS and GLONASS data bit streams with few modifications. Finally, the method proposed is simple enough as to be implemented on real-time embedded GNSS receivers.